A Child's HLA-DRB1 genotype increases maternal risk of systemic lupus erythematosus. (November 2016) - Cruz, Giovanna I.; Shao, Xiaorong; Quach, Hong; Ho, Kimberly A.; Sterba, Kirsten; Noble, Janelle A.; Patsopoulos, Nikolaos A.; Busch, Michael P.; Triulzi, Darrell J.; Wong, Wendy S.W.; Solomon, Benjamin D.; Niederhuber, John E.; et al.
Abstract: Systemic lupus erythematosus (SLE) disproportionately affects women of reproductive age. During pregnancy, women are exposed to various sources of fetal material possibly constituting a significant immunologic exposure relevant to the development of SLE. The objective of this study was to investigate whether having any children who carry DRB1 alleles associated with SLE increase the risk of maternal SLE. This case-control study is based on the University of California, San Francisco Mother-Child Immunogenetic Study and from studies at the Inova Translational Medicine Institute. Analyses were conducted using data for 1304 mothers (219 cases/1085 controls) and their respective 1664 children. We selected alleles based on their known association with risk of SLE ( DRB1*03:01, * 15:01, or * 08:01) or Epstein-Barr virus (EBV) glycoproteins (* 04:01 ) due to the established EBV association with SLE risk. We used logistic regression models to estimate odds ratios (OR) and 95% confidence intervals (CI) for each allele of interest, taking into account maternal genotype and number of live births. We found an increase in risk of maternal SLE associated with exposure to children who inherited DRB1*04:01 from their father (OR 1.9; 95% CI, 1.1–3.2), among *04:01 allele-negative mothers. Increased risk was only present among mothers who were positive for one or more SLE risk-associated alleles (* 03:01, *15:01 and/or * 08:01 ). We did not find increased risk of maternal SLE associated with any other tested allele. These findings support the hypothesis that a child's alleles inherited from the father influence a mother's subsequent risk of SLE. Highlights: A child's DRB1 genotype is associated with increased risk of maternal SLE. DRB1*04:01 inherited from the father is associated with a 2-fold risk of SLE. Risk was only increased among mothers who carry DRB1 *03:01, *15:01 and/or *08:01.